2013
DOI: 10.1097/grf.0b013e31827adf91
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Management of Neonatal Abstinence Syndrome in a Community Hospital

Abstract: Neonatal abstinence syndrome has become a growing concern in infants born to substance-abusing mothers in the State of Florida. At Sarasota Memorial Hospital in Sarasota, FL, methadone and morphine treatment strategies have been formulated to manage symptomatic neonates after birth. We report our findings over a 5-year period utilizing each of these protocols in a community hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…According to the Centers for Disease Control and Prevention (CDC), the incidence of NAS increased 3‐fold in the United States from 1999 to 2013 . Previous studies have shown that the incidence of NAS in Florida increased disproportionally by >10‐fold during a similar period . Identifying the underlying factors associated with this increase is important for prioritizing strategies for NAS prevention, especially in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention (CDC), the incidence of NAS increased 3‐fold in the United States from 1999 to 2013 . Previous studies have shown that the incidence of NAS in Florida increased disproportionally by >10‐fold during a similar period . Identifying the underlying factors associated with this increase is important for prioritizing strategies for NAS prevention, especially in Florida.…”
Section: Introductionmentioning
confidence: 99%
“…18 In a study from Florida, the number of neonates who had NAS and were admitted to the NICU increased by 10-fold from 2005 to 2011. 21 Increases in the incidence of NAS have been reported uniformly across community hospitals, teaching hospitals, and children' s hospitals. 22 All communities and all ethnicities have been affected.…”
Section: Incidencementioning
confidence: 99%
“…49 Morphine dose can also be escalated by .10% for higher scores. 21 Methadone can be substituted for morphine for opioid withdrawal. Cardiopulmonary monitoring of the infant is preferred during the acute stage.…”
Section: Figurementioning
confidence: 99%
“…17, 18 Others, however, have abandoned outpatient management because of concerns raised by community pediatricians regarding NAS management. 19 …”
Section: Discussionmentioning
confidence: 99%